2004
DOI: 10.1177/153537020422900301
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Significance and Metabolism of Very Long Chain Fatty Alcohols and Acids from Dietary Waxes

Abstract: Very long chain fatty alcohols obtained from plant waxes and beeswax have been reported to lower plasma cholesterol in humans. This review discusses nutritional or regulatory effects produced by wax esters or aliphatic acids and alcohols found in unrefined cereal grains, beeswax, and many plant-derived foods. Reports suggest that 5-20 mg per day of mixed C24-C34 alcohols, including octacosanol and triacontanol, lower low-density lipoprotein (LDL) cholesterol by 21%-29% and raise high-density lipoprotein choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 91 publications
7
120
0
Order By: Relevance
“…For this reason, the concentrations observed represent only non-esterified circulating policosanol, which explains the low values previously reported (Marrero and González-Bravo, 2001;Menendez et al, 2005, Gonzalez-Bravo et al, 1996. Furthermore, several studies have described the hydrolysis of wax as a necessary step for the absorption of fatty alcohols and fatty acids (Hargrove et al, 2004;Place, 1992). Based on this contention, our results suggest that a major fraction of policosanol is re-esterified inside the enterocyte, in agreement with the absorption of dietary lipids such as cholesterol, in which case esterification is produced by the catalytic action of the enzyme acyl-CoA cholesterol acyltransferase (Buhman et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For this reason, the concentrations observed represent only non-esterified circulating policosanol, which explains the low values previously reported (Marrero and González-Bravo, 2001;Menendez et al, 2005, Gonzalez-Bravo et al, 1996. Furthermore, several studies have described the hydrolysis of wax as a necessary step for the absorption of fatty alcohols and fatty acids (Hargrove et al, 2004;Place, 1992). Based on this contention, our results suggest that a major fraction of policosanol is re-esterified inside the enterocyte, in agreement with the absorption of dietary lipids such as cholesterol, in which case esterification is produced by the catalytic action of the enzyme acyl-CoA cholesterol acyltransferase (Buhman et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Taking into account these antecedents, our study considered the kinetics not only of the more abundant alcohols of the policosanol mixture (octacosanol and triacontanol), but also of the respective fatty acids produced from their metabolism (octacosanoic acid and triacontanoic acid). The long-chain octacosanoic and triacontanoic fatty acids maintained low plasma concentrations in the time period assessed, showing a tendency to increase as their precursors disappeared from circulation, results that are consistent with the metabolic pathway proposed for policosanol (Haim and Videla, 2008;Menéndez et al, 2005;Hargrove et al, 2004). Nevertheless, a proportion lower than 33% of policosanol disappearance can be explained by its metabolic conversion into the respective long-chain fatty acids.…”
Section: The Oleic Acid Esterification Of Policosanol Increases Its Bsupporting
confidence: 69%
“…Furthermore, beeswax has a faint honey-like odor that might be effective together with fruit flavors. Nevertheless, clinical studies have revealed that beeswax had plasma cholesterol lowering and antimicrobial effects, thus inclusion of beeswax into human diet might be used for reducing the risk of diseases related with high cholesterol 30 . Table 4 The colour, peroxide value and induction period of the fish oil and fish oil organogels during the 90 days storage period at 4℃ (Mean±Sd).…”
Section: Storage Stability Of the Avored Organogelsmentioning
confidence: 99%
“…Dietary WEs are an important source of very long chain fatty alcohols and acids that exert regulatory roles in the cholesterol metabolism ( 11 ). Naturally occurring WEs usually form complex mixtures composed of many molecular species.…”
mentioning
confidence: 99%